Molecular logic for cellular specializations that initiate the auditory parallel processing pathways - Junzhan Jing; Ming Hu; Tenzin Ngodup; Qianqian Ma; Shu-Ning Natalie Lau; M. Cecilia Ljungberg; Matthew J. McGinley; Laurence O. Trussell; Xiaolong Jiang (Nature Communications)
Abstract The cochlear nuclear complex (CN), the starting point for all central auditory processing, encompasses a suite of neuronal cell types highly specialized for neural coding of acoustic signals. However, the molecular logic governing these specializations remains unknown. By combining single-nucleus RNA sequencing and Patch-seq analysis, we reveal a set of transcriptionally distinct cell populations encompassing all previously observed types and discover multiple hitherto unknown subtypes with anatomical and physiological identity. The resulting comprehensive cell-type taxonomy reconciles anatomical position, morphological, physiological, and molecular criteria, enabling the determination of the molecular basis of the specialized cellular phenotypes in the CN. In particular, CN cell-type identity is encoded in a transcriptional architecture that orchestrates functionally congruent expression across a small set of gene families to customize projection patterns, input-output synaptic communication, and biophysical features required for encoding distinct aspects of acoustic signals. This high-resolution account of cellular heterogeneity from the molecular to the circuit level reveals the molecular logic driving cellular specializations, thus enabling the genetic dissection of auditory processing and hearing disorders with a high specificity.